Efficacy and cerebral mechanisms of acupuncture for chronic obstructive pulmonary disease: study protocol for a multicenter, randomized controlled neuroimaging trial - Chen, Xugui; Xiong, Chan; Xiao, Wei; Du, Longyi; Liu, Meilu; Yu, Yan; Liao, Chunyu; Zhang, Chengshun; Li, Yu; Mao, Bing; Fu, Juanjuan (Frontiers in Neurology, 2024)
Introduction Although acupuncture is recommended by chronic obstructive pulmonary disease (COPD) treatment guidelines owing to its effects on dyspnea, the underlying neurobiological mechanisms of these effects remain unclear. This study aims to evaluate the efficacy of acupuncture in patients with stable COPD and explore the possible involvement of specific brain regions. Methods This is a prospective, multicenter, single-blind, randomized controlled trial. A total of 90 participants will be recruited from three centers and will be randomly assigned in a 1:1 ratio to undergo acupuncture at acupoints on the disease-affected meridian (DAM) or non-acupoints on the non-affected meridian (NAM), in addition to routine pharmacological treatments. All participants will undergo 30 min of acupuncture three times a week for 8 weeks and will be followed up for 12 months. The primary outcome will be the severity of dyspnea, as measured using the Borg Dyspnea Scale and a visual analog scale at rest and after exercise. The secondary outcomes will include the multidimensional profile of dyspnea using Dyspnea-12, the modified Medical Research Council Dyspnea Scale, and the COPD assessment test; quality of life assessments using St George's Respiratory Questionnaire and the Hospital Anxiety and Depression Scale; and additional measurements of exacerbation frequency, pulmonary function, and the 6-min walking distance. Magnetic resonance imaging (MRI) will be performed before and after exercise to explore the potential neurobiological mechanisms of exertional dyspnea. Anxiety and depression will be measured and analyzed for their correlation with the activation of specific brain areas involved in dyspnea. Discussion This randomized controlled trial aims to use a multidimensional evaluation of the efficacy of acupuncture in relieving dyspnea in patients with COPD in terms of emotion and quality of life and explore the neurobiological mechanisms underlying the effects of acupuncture on dyspnea from an imaging perspective. It is expected to provide strong evidence to support the use of acupuncture in relieving dyspnea in patients with COPD and those with aother diseases involving dyspnea. Additionally, it provides novel insights into the central mechanisms of acupuncture intervention and dyspnea. Trial registration Chinese Clinical Trial Registry (https://www.chictr.org.cn/): ChiCTR2300071725.